Radiotherapy for lentigo maligna: a literature review and recommendations for treatment. (1st January 2014) - Fogarty, G.B.; Hong, A.; Scolyer, R.A.; Lin, E.; Haydu, L.; Guitera, P.; Thompson, J.
Summary: Lentigo maligna (LM) incidence is increasing. LM frequently involves the face near critical anatomical structures and as a consequence clinical management is challenging. Nonsurgical therapies, including radiotherapy (RT), are increasingly used. Evidenced‐based treatment guidelines are lacking. We conducted a review of previously published data analysing RT treatment of LM. A search of PubMed, Embase and Medline databases to June 2012 identified nine clinical studies that examined the use of RT for LM treatment in at least five patients. Nine studies described 537 patients with LM treated with definitive primary RT, between 1941 and 2009, with a median reported follow‐up time of 3 years. Eight articles could be reviewed for oncological outcome data. There were 18 recurrences documented in a total of 349 assessable patients (5%). Salvage was successful in the majority of recurrent LM cases by using further RT, surgery or other therapies. Progression to LM melanoma (LMM) occurred in five patients (five out of 349, 1·4%) who all had poor outcomes. There were five marginal recurrences documented out of 123 assessable patients (4%). There were eight in‐field recurrences documented with either LM (five) or LMM (three) out of 171 assessable patients (5%). A series of recommendations were then developed for RT parameters for treatment of LM. These parameters include treatment volume, dose, dose per fraction and outcome measures. These may be of use in prospective data collection.